Para além do Minha Casa Minha Vida: Uma política de habitaç\~ao de interesse social? - Renato Balbim; Cleandro Krause; Vicente Correia Lima Neto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The "Minha Casa Minha Vida" program (MCMV) started in 2009 and was afterwards elevated to the status of Brazilian housing policy. Since its creation the appearance of other alternatives for housing provision has been restricted. This paper performs a diagnosis of the recent housing policy in Brazil, in particular the MCMV's various forms of action. The article also points, as criticism, the spatial mismatch between the housing shortage and the housing production, and the unequal treatment of the housing shortage, when disaggregated into its four components, among other aspects. In order to overcome these challenges, we detail two alternatives that, combined or independent, may expand the fulfilment of housing needs: the social production of housing and the social housing rental service.
Keywords: R21; R28; R31; 330; Minha Casa Minha Vida; social production of housing; social housing rental service; housing shortage